Efektivitas Model Pembelajaran Inquiry terhadap Hasil Pembelajaran Biologi Siswa Kelas X SMA Negeri 6 Lubuklinggau - Destien Atmi Arisandy; Linna Fitriani; Flora Ghassani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effectiveness of inquiry learning models on the learning outcomes of biology students in class X SMA Negeri 6 Lubuklinggau. This type of research is quantitative research with experimental research methods. The population used was all students of class X SMA Negeri 6 Lubuklinggau, which consisted of 213 students and a sample of researchers, namely class X.1 for the experimental class and class X.2 for the control class. Data collection using tests. The data obtained were analyzed using t-test. From the research that has been done, it is obtained the post-test data of the experimental class and the control class with α = 0.05 obtained t-count = 4.06 and t-table = 1.67, because t-count> t-table, means the average score for the experimental class is higher than the control class, so it can be concluded that the inquiry learning model is effective for learning biology in class X students of SMA Negeri 6 Lubuklinggau. Keywords: efektivitas, inquiry learning model, results of studying biology.